(untitled) (European Journal of Marketing and Economics, 2021)
The paper studies organizational support with respect to Human Resource Management during the COVID-19 pandemic. It examines HRM initiatives regarding changing in jobs, working routine, workplaces, and remote working conditions. The paper analyses how HR managers supported employees during the pandemic and how top-management encouraged employee wellbeing. It also explores whether HRM practice and employee emotions are a strategic focus for companies. Quantitative data for this research was collected with survey from forty-eight organizations located in Georgia. The findings suggest that HRM supported staff with helping them to update their skills for remote working, established flexible working hours, and adopted less strict policies regarding performance management. Additionally, HR managers have been encouraged by the top-management in implementing initiatives concerning employee physical and emotional wellbeing. Furthermore, HRM should be a strategic focus for any organization to lay foundation of employee relationship and organizational culture in order to overcome difficulties and adapt to the changes. The novelty of the research highlights the importance of HRM practice when economies are facing the threat of recession. It contributes to HRM in terms of supporting employees during the pandemic as well as from the top-management perspective to promote HR initiatives, and paves the way for further studies in this field.